Improvement of Nutrients Removal from Domestic Wastewater by Activated-Sludge Encapsulation with Polyvinyl Alcohol (Pva) - Villamar-Ayala, C (Taylor and Francis Inc., 2019)
Conventional activated-sludge (AS) technologies are deficient for nutrient removal because they require specific floc characteristics. Therefore, the encapsulated AS with polyvinyl alcohol (PVA) will favor floc’s formation that removes nutrients. The applied method was based on monitoring the removal of organic matter and nutrients (NH4 +, NO3 -, NO2 -, PO4 3-) from synthetic domestic wastewater using laboratory-scale AS. The experimental reactors were operated at 8 h as optimized Hydraulic Retention Time (HRT). The sludge characteristics evaluation was carried out through the Sludge Volumetric Index (SVI), Food/Microorganism ratio (F/M), and Mixed Liquor Volatile Suspended Solids (MLVSS). Other specific floc characteristics, such as zeta potential and effective diameter were also evaluated. The results showed that the encapsulated AS with PVA favors nitrogen and phosphorous removal up to 35% but it did not improve organic matter removal. In addition, encapsulated AS with PVA has the characteristics of filamentous sludge (F/M: 0.7 g COD g−1 MLVSS d−1) with good settleability conditions (SVI: 43 mL g−1 MLSVS h−1) and low zeta potential (ZP: -0.9 mV), which favors its separation from the liquid phase. In conclusion, the encapsulation of AS with PVA improves nutrient removal by improving floc characteristics. © 2019, © 2019 Taylor & Francis Group, LLC.